A way of Supporting Non-Arabic Speakers in Identifying Arabic Letters and Reading Arabic script in our new E-Learning System - Ahmed Mosa; Katsuhikor Kakehi (European Alliance for Innovation (EAI), 2015)
This paper reports how a new multimedia, for developing Arabic e-Learning, supports the beginners of non-Arabic speakers in identifying Arabic letters in a word by using colored script, and reading Arabic script by using our new reversed phonetics, right to left. In Arabic, letters are connected to each other in the word. Each Arabic letter has three different figures according to its position in a word (beginning, middle or end). Users' study was conducted with 77 examinees in Japan to find which one is preferable for identifying letters of two alternatives: coloring letters or separating letters with spaces. Results showed that colored alternative is preferable. Another study was conducted with another 20 examinees in Japan to confirm that our new system supports the beginners in reading Arabic letters comparing with the conventional phonetic system. We develop an e-learning system incorporates our multimedia to support learners in identifying and reading Arabic script by themselves.